PROYEKSI STOKASTIK PRODUKSI PADI DI INDONESIA - Dwitia, Agnesya; Hudoyo, Agus; Nugraha, Adia (Lampung University, 2019)
Rice is the staple food for Indonesian people and Indonesia was in self-sufficiency for rice in 1984. Based on the Agricultural Ministry’s Strategic Planning for 2015 – 2019, the government targeted that the self-sufficiency in rice in 2019 by 82,078 million tons of the rice production. It is better that the production is stochastically forecasted in form of the interval of projection possibility with the certain probability level. Therefore, the objective of this research is to know the growth of rice production and to stochastically forecast it. The data used in this research is the production of rice in the period of 1961 – 2015 obtained from the Food and Agriculture Organization (FAO), and the Central Bureau of Statistics (CBS), Indonesia. The research data is analyzed by econometric method. The result revealed that the rice production would be 77,487 million tons in 2019 and it was 95% confidence interval would be between 74,901 and 80,071 million tons. The growth rate of the rice production in 2018 – 2020 would be 0.6 percent per year. We could conclude that the government target of the rice production was higher than the result of stochastic forecasting.Key words: forecast, paddy, production